Low-energy EDX - A novel approach to study stress corrosion cracking in SUS304 stainless steel via scanning electron microscopy - Meisnar, M; Lozano-Perez, S; Moody, M; Holland, J (Elsevier, 2014)
Intergranular stress corrosion cracking (IGSCC) in type SUS304 stainless steels, tested under pressurized water reactor (PWR) primary water conditions, has been characterized with unprecedented spatial resolution using scanning electron microscopy (SEM) and novel low-energy (~3. kV) energy dispersive X-ray spectroscopy (EDX). An advancement of the large area silicon drift detector (SDD) has enhanced its sensitivity for X-rays in the low-energy part of the atomic spectrum. Therefore, it was possible to operate the SEM at lower accelerating voltages in order to reduce the interaction volume of the beam with the material and achieve higher spatial resolution and better signal-to-noise ratio. In addition to studying the oxide chemistry at the surface of intergranular stress corrosion cracks, the technique has proven capable of resolving Ni enrichment ahead of some crack tips. Active cracks could be distinguished from inactive ones due to the presence of oxides in the open crack and Ni-rich regions ahead of the crack tip. Furthermore, it has been established that SCC features can be better resolved with low-energy (3. kV) than high-energy (12. kV) EDX. The low effort in sample preparation, execution and data analysis makes SEM the ideal tool for initial characterization and selection of the most important SCC features such as dominant cracks and interesting crack tips, later to be studied by transmission electron microscopy (TEM) and atom probe tomography (APT). © 2014 Elsevier Ltd.